Bio-efficacy and economic assessment of pre- and post-emergence herbicides in weed management of chickpea - Pritika, T; Amit, D; Shivani, S; Sonali, S; Abha, T; Sunitha, F; Kanika, S; Diksha (Plant Science Today, 2026)
A field investigation was conducted during two consecutive rabi seasons at Research Farm of Maharishi Markandeshwar (Deemed to be University), Ambala, Haryana, India to assess the efficacy of various herbicide treatments and their impact on weed control, yield and economics in chickpea cultivation. The experiment was laid out in a randomised block design (RBD) with three replications. Nine herbicidal treatments were evaluated, along with a weed free and weedy check. Among pre-emergence (PRE) herbicides pendimethalin, oxyfluorfen and pendimethalin + imazethapyr (RM) were applied alone or in combination with hand weeding (HW). Among post-emergence (PoE) herbicides oxyfluorfen, topramezone and imazethapyr + imazamox (RM) were applied. Among PRE herbicides, pendimethalin + imazethapyr (RM) PRE followed by one HW (T7) recorded with highest weed control efficiency (91.8 and 87.2) and percent weed control (86.5 and 86.4) during first and second year of experiment. While among PoE, Imazethapyr + imazamox (RM), PoE at 100 g ha-1 (T9) recorded with excellent weed control efficiency and percent weed control of narrow-leaf, broad-leaf and total weeds at all stages of crop growth during both years of experiment. Severe phytotoxicity (80 % and 85 %) to chickpea crop upon PoE application of oxyfluorfen (T5). Application of pendimethalin + imazethapyr (RM) followed by one HW recorded with 56.1 and 52.7 % increase in seed yield over weedy check during first and second year of experiment, respectively. Maximum benefit to cost (B:C) was calculated from T6- pendimethalin + imazethapyr (RM) PRE (2.04 and 1.77) followed by T7 (1.98 and 1.82) and minimum from T5 (0.64 and 0.59) during first and second year, respectively.